2020
DOI: 10.3390/ani10091711
|View full text |Cite
|
Sign up to set email alerts
|

The Fermentation Process Improves the Nutritional Value of Rapeseed Cake for Turkeys—Effects on Performance, Gut Bacterial Population and Its Fermentative Activity

Abstract: This experiment investigated the potential inclusion of fermented rapeseed cake (FRC) in turkey diets. The turkeys received diets either not supplemented (C) or supplemented with raw rapeseed cake (RRC) or FRC at 150 g/kg diet. In comparison with RRC, turkeys receiving FRC achieved significantly higher final BW comparable with that noted in the control group. The dietary inclusion of FRC increased the concentrations of propionic and valeric acid in the cecal digesta compared with the control group, and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In contrast, an insufficient supply of dietary Lys, below the chickens’ requirements, was reported to induce protein degradation to satisfy muscle requirements for protein synthesis, which suggests that the regulatory system could preferentially use Lys and make it available for cecal bacteria due to its key role in protein synthesis [ 41 ]. However, it should be noted that the SCFA profile was not disrupted in terms of the contribution of major SCFA, including C2, C3 and C4, which are formed in the greatest abundance in the ceca of turkeys [ 42 ]. However, in the present study, the SCFA-associated changes in the cecal digesta were probably affected by the larger amount of digesta and its lower pH in turkeys fed high-Lys diets, which fully corresponded to the functional response of the gut, described above.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, an insufficient supply of dietary Lys, below the chickens’ requirements, was reported to induce protein degradation to satisfy muscle requirements for protein synthesis, which suggests that the regulatory system could preferentially use Lys and make it available for cecal bacteria due to its key role in protein synthesis [ 41 ]. However, it should be noted that the SCFA profile was not disrupted in terms of the contribution of major SCFA, including C2, C3 and C4, which are formed in the greatest abundance in the ceca of turkeys [ 42 ]. However, in the present study, the SCFA-associated changes in the cecal digesta were probably affected by the larger amount of digesta and its lower pH in turkeys fed high-Lys diets, which fully corresponded to the functional response of the gut, described above.…”
Section: Resultsmentioning
confidence: 99%
“…The research was conducted in accordance with the methodology of the Authors' previous research [30], [31].…”
Section: Bacterial Dna Extraction and 16sr Rnasequencingmentioning
confidence: 99%
“…The research was conducted in accordance with the methodology of the Authors' previous research [30], [31]. For sequencing, the individual libraries were diluted for 4 nM, denaturated with 10 mM Tris pH 8.5, and spiked with 20% (v/v) of PhiX.…”
Section: Bacterial Dna Extraction and 16sr Rnasequencingmentioning
confidence: 99%
“…As the main end products of fermentation, SCFAs stabilize the composition and function of the gut microbiome, and constitute an extra source of energy, which can slightly improve the growth performance of birds. Our previous study (Drażbo et al, 2020) has shown that the fermentation process improved the nutritional value of RC, and exerted beneficial effects on SCFA concentrations and the activities of bacterial glycolytic enzymes.…”
mentioning
confidence: 95%
“…According to Zhu et al (2020), fermented feeds can improve the laying performance, antioxidant and immune status of layers. In addition, studies have shown that fermented diets have the potential to improve intestinal digestive function and morphology, and to modulate the gut microbial ecosystem in poultry (Hu et al, 2016;Drażbo et al, 2020;Lv et al, 2022). In a study by Elbaz (2021), fermented canola meal improved nutrient digestibility in broiler chickens, most likely due to the reduction of the pathogenic load (microbial modulation) in the gut, which positively affected nutrient absorption and increased the nutritional value of canola meal.…”
mentioning
confidence: 99%